2017
DOI: 10.3897/zookeys.679.12560
|View full text |Cite
|
Sign up to set email alerts
|

Description of the immature stages of Larinus vulpes and notes on its biology (Coleoptera, Curculionidae, Lixinae)

Abstract: Mature larva and pupa of Larinus vulpes (Olivier, 1807) (Curculionidae: Lixinae: Lixini) are morphologically described for the first time and compared with known larvae and pupae of other Larinus species. Very high counts of larval body setae (pronotum with more than 25 setae and postdorsum on meso- and metathorax and also on abdominal segments I–VII with more than 12 setae) are characteristic features of the nominotypical subgenus Larinus. The biology of the species was studied in Ukraine. Echinops ruthenicus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 46 publications
2
5
0
Order By: Relevance
“…The mature larvae of the subfamily Lixinae were characterized by three diagnostic features [44]: the increased number of pds (1) on the meso- and metathorax and (2) abdominal segments I–VII, and (3) the increased number of setae on the epipharyngeal lining ( als ); i.e., more than the most frequent number of setae in weevils (for details, see [11]). These differential features of mature larvae were confirmed in all known descriptions from the tribe Cleonini [9,10,11,27,43], and all known species from the Lixini tribe fit this diagnosis (genus Larinus [45,46,47,48]; Lixus species [27,45,49,50,51,52,53,54,55]; and Rhinocyllus conicus [37]).…”
Section: Resultssupporting
confidence: 54%
“…The mature larvae of the subfamily Lixinae were characterized by three diagnostic features [44]: the increased number of pds (1) on the meso- and metathorax and (2) abdominal segments I–VII, and (3) the increased number of setae on the epipharyngeal lining ( als ); i.e., more than the most frequent number of setae in weevils (for details, see [11]). These differential features of mature larvae were confirmed in all known descriptions from the tribe Cleonini [9,10,11,27,43], and all known species from the Lixini tribe fit this diagnosis (genus Larinus [45,46,47,48]; Lixus species [27,45,49,50,51,52,53,54,55]; and Rhinocyllus conicus [37]).…”
Section: Resultssupporting
confidence: 54%
“…X reduced to four anal lobes of unequal size, dorsal one by far the largest, ventral one very small". These different traits of mature larvae of Lixini have been confirmed in several descriptions concerning the genus Larinus [3,22,[32][33][34][35][36][37][38] and the genus Lixus [20,21,24,31,33,34,[39][40][41] but there were also more exceptions [21,22] than those presented in Gosik and Wanat [31]. All Larinus species differ from Lixus species, mainly by their (1) U-shaped premental sclerite (vs. Lixus species with a trident-shaped premental sclerite), (2) abdominal segments I-VII with three folds (vs. four folds), and (3) pupae with distinct urogomphi (vs. indistinct).…”
Section: A Comparison With Larvae Of Other Lixinisupporting
confidence: 61%
“…All Larinus species differ from Lixus species, mainly by their (1) U-shaped premental sclerite (vs. Lixus species with a trident-shaped premental sclerite), (2) abdominal segments I–VII with three folds (vs. four folds), and (3) pupae with distinct urogomphi (vs. indistinct). However, an exception is represented by most species of the nominotypic subgenus of the genus Larinus , whose chaetotaxy on the body is markedly different [ 22 ]. Skuhrovec et al [ 22 ] also identified the morphological features of larvae and pupae, which significantly distinguish the subgenus Larinus from the other subgenera, Phyllonomeus Gistel, 1856 and Larinomesius .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations